Annual and interannual complementarities of renewable energy sources in Colombia. (December 2020) - Henao, Felipe; Viteri, Juan P.; Rodríguez, Yeny; Gómez, Juan; Dyner, Isaac
Abstract: The Colombian power sector is highly dependent on hydroelectricity, making it vulnerable to both annual dry seasons and the droughts brought by the El Niño-Southern Oscillation (ENSO). One efficient way to reduce such vulnerabilities is by introducing renewable energies that may complement the availability of hydroelectricity. This paper explores the degree of complementarity between solar and wind resources in Colombia and the country's hydropower sector, on both annual and interannual scales. Various correlation analyses are performed over four climatic variables: water inputs (runoff), precipitation, solar radiation, and wind speed, plus the Oceanic Niño Index (ONI), which helps to characterize ENSO events. The analysis is carried out over different geographic locations and seasons. The results indicate that solar and wind resources, particularly those in the Caribbean Coast and the central Andes regions, complement the hydropower sector during both the dry seasons of the annual climatological cycle and ENSO's warm and cold phases. Also, they show that complementarity varies, not just with the type of sources and location, but also with the seasons of the year and ENSO's stage of development. This paper provides an enhanced perspective on the behavior of renewables and offers an alternative viewpoint for designing the future expansion of power systems. Graphical abstract: Image 1 Highlights: Annual and interannual complementarities between renewable energies are explored. Solar and wind can complement hydropower during the annual dry seasons and ENSO. The Caribbean Coast and Andes regions have the largest complementarity potential. Complementarity varies through yearly seasons and ENSO's development stages.